Productivity, credit, risk, and the demand for weather index insurance in smallholder agriculture in Ethiopia. (24th May 2013) - McIntosh, Craig; Sarris, Alexander; Papadopoulos, Fotis
Abstract The article explores the relationship between fertilizer use and the demand for weather index insurance (WII) among smallholder farmers in Ethiopia. We examine whether fertilizer use is profitable under current smallholder production conditions, whether risk‐related factors affect fertilizer use, and we estimate the returns to inputs in the agricultural production function in the absence of insurance. We then study how these primitives of agricultural production functions relate to insurance demand. The study compares a survey‐based estimate of willingness to pay with actual uptake for the weather insurance, finding the stated and actual demand to be almost completely uncorrelated. While those with high marginal returns to inputs say they would purchase insurance, only those with low marginal returns actually do, consistent with the stated purpose of the product as input insurance. Insurance demand proves to be highly responsive to the existence and amount of randomly allocated insurance vouchers.